Strategi Pengendalian Kebakaran Hutan Dan Lahan Di Provinsi Riau - Nabila Noor Aliffia; Aryo Sasmita; Gunadi Priyambada (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Forest and land fires can produce Greenhouse Gases (GHGs), most of which are in the form of carbon dioxide (CO2) which are harmful to health and the environment. The purpose of this study was to determine the appropriate forest and land fire control strategy to be applied in Riau Province. The method used in this study is by referring to government regulations and regional regulations of Riau Province. The results showed that the forest and land fire control strategy was divided into 3 activities, namely: forest and land fire prevention, forest and land fire suppression, and post forest and land fire control.Keywords: Control strategies, Forest Fires, handling, prevention, suppression